Dynamic Hierarchical Virtual Button-based Hand Interaction for Wearable AR - Kim, Hyejin; Widjojo, Elisabeth Adelia; Hwang, Jae-In (2015 IEEE VIRTUAL REALITY CONFERENCE (VR), 2015)
This paper presents a novel bare-hand interaction method for wearable AR (augmented reality). The suggested method is using hierarchical virtual buttons which are placed on the image target. Therefore, we can provide precise hand interaction on the image target surface (while using wearable AR). The method operates on a wearable AR system and uses an image target tracker to make occlusion-based interaction button. We introduce the hierarchical virtual button method which is adequate for more precise and faster interaction with augmented objects.